Evaluating the growth and development of black soldier fly (BSF) (Hermetia illucens (L.) (DIPTERA: STRATIOMYIDAE) larvae reared on different agricultural waste materials - Fairuz Liyana Mohd Rasdi; Ahmad Razali Ishak; Siti Norashikin Mohamad Shaifuddin; Nazri Che Dom; Siti Rohana Mohd Yatim; Megat Azman Megat Mokhtar; Razi Ikhwan Md Rashid; Pui, Wee Hua; Zulhisyam Abdul Kari; Hisham Atan Edinur (Penerbit Universiti Kebangsaan Malaysia, 2023)
The black soldier fly (BSL), Hermetia illucens (L.), is a beneficial insect that helps manage high concentrations of animal manure and other biosolids in tropical and warm-temperate areas. Bioremediation with black soldier fly larvae (BSFL) can turn biosolids into high-value biomass (proteins, oils, lipids, and chitin). This study explored the effects of three agricultural wastes as feedstocks for the growth and development of BSFL. A total of 1000 7-day-old BSFLs were reared separately in containers containing either palm kernel extract (PKE), soybean waste (SW), or coconut milk waste (CMW). The effect of feeding substrate on larval growth and development was determined for ten days by daily measurements of the BSFL’s length and weight. BSFL reared on PKE substrate resulted in the highest mean length (22.67±2.31 mm) and weight growth (0.27±0.02 g), followed by BSFL reared on SW (length: 18.67±1.53 mm; weight: 0.20±0.02 g) and CMW (length: 18.33±0.58mm; weight: 0.15±0.01 g). Bioconversion rate of BSFL was also found to differ across treatments; BSFL reared on PKE grows and converts substrates twice as fast as those fed on SW or CMW. This work then examines the effects of several SW:PKE ratios (20:80; 80:20; 30:70; 70:30 and 50:50) on BSFL growth. The weight (0.28±0.04 g) and length (22.67±2.52 mm) of BSFL were highest when SW:PKE ratio of 80:20 is used. High content of SW resulted in a significant increase in BSFL length (6.76%-15.25%) and weight (23.54%-64.71%). Therefore, it can be concluded that substrate feed type has a substantial effect on BSFL’s growth and development.